CFD ANALYSIS OF MINI VENTURI-TYPE AIR FLOWMETERS FOR LAB-SCALE APPLICATIONS - Demir, Selami (YILDIZ TECHNICAL UNIV, 2020)
Being one of the cheapest devices for air flow measurement within a wide range of flowrates, Venturi-type air flowmeters (VTAFs) can also be used for measuring very small air flowrates, usually less than 50 to 100 liters per minute, which is usually encountered in lab-scale applications. This study presents a model-based evaluation of VTAFs for lab-scale applications. The pressure and velocity fields in mini VTAFs were calculated by computational fluid dynamics (CFD) model using Ansys Fluent (TM). Results showed that sensitive and accurate measurements of volumetric flowrate can be achieved using mini VTAFs. A diameter ratio of 0.6 for the venturi throat provides a minimum detection limit of 2.46 LPM while an overall pressure drop of around 115 Pa at an air flowrate of 50 LPM at 20 degrees C.
Keywords: Air flow; mesasurement; lab-scale applications; venturi flowmeters; FLOW; PRESSURE; METER; MODEL; Engineering